PARTISIPASI MASYARAKAT DALAM PENGELOLAAN AIR BERSIH DI NAGARI LIMAU LUNGGO KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Susilawati, Sri - (STKIP PGRI Sumbar, 2014)
This purposes of this research is to describe and to analyze the participation, interms of: 1) Attention. 2) Measures. 3) Responsibility in the management of water inNagari Limau Lunggo District Lembang Jaya Regency of Solok.Kind of this research is qualitative research and the reseacrher conducts thisresearch at Nagari Limau Lunggo Lembang Jaya. Generally, to do this research, theresearcher needs popolation and the population of this research is 25 person. To colletthe data, the researcher uses instrumentation such as documentation, observation andinterviews. The accuracy of the data was tested by using triangulation of data, datacollected were analyzed by using a model consisting of purposive data selection, datareduction, data display, data interpretation and conclusion.The results showed that: community participation in water management in NagariLemons Lunggo District Lembang Jaya Solok district are 1) the lack of public attention inNagari Limau Lunggo to improve water management. 2) Measures shown limau Lunggovillagers is also less. 3) Responsibility community in Nagari limau Lunggo shows lesswell in clean water management. Judging from the attention, actions and responsibilitiesthat exist Limau Lunggo Nagari region is that the public expects the governments effortsso that water can flow evenly.